Effect of Intrathecal Fentanyl on Shivering During Spinal Anesthesia - Thapa, Ajay Singh; Sah, Rakesh; Yadav, Rajesh Kumar; Bhattarai, Anish (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Perioperative shivering is a common complication following spinal anesthesia. Apart from the obvious discomfort, shivering is associated with a number of potentially deleterious sequels. The objective of this research is to study the effect of intrathecal fentanyl on shivering. Methods Retrospectively two hundred patients were included and divided into two equal groups. In group A, 3.5 ml of 0.5% heavy bupivacaine was mixed with 25 mcg (0.5 ml) of fentanyl to make 4 ml solution out of which the enrolled patients received 3.5 ml of the mixed solution. Group B received 3.5 ml of 0.5% plain heavy bupivacaine. Modified bedside shivering assessment scale was used to score the intensity of shivering. Results In group A, 16 patients (16%) had severe shivering, 30 patients (30%) had moderate shivering and 46 (46%) had mild shivering. Rest of the patients (8%) did not experience shivering. In group B, all the patients had shivering. Severe shivering was observed in 28 patients (28%), moderate shivering was observed in 62 patients (62%) and mild shivering in 10 patients (10%). Conclusions Fentanyl as an adjuvant to heavy bupivacaine during spinal anesthesia decreases the incidence and severity of shivering compared to bupivacaine alone.